PENGETAHUAN BERHUBUNGAN DENGAN EFIKASI DIRI DALAM MEMBERIKAN PERTOLONGAN PERTAMA KECELAKAAN LALU LINTAS PADA REMAJA - Putri, Nyoman Anggun Septiana; Suindrayasa, I Made; Kamayani, Made Oka Ari (Coping: Community of Publishing in Nursing, 2022)
Knowledge of first aid for traffic accidents is everything that a person knows regarding to the immediate assistance given to accident victims before being handled by paramedics. Knowledge is closely related to self-efficacy. Adolescents are one who can provide first aid. Preliminary studies show that some things related to first aid are already known by adolescents, but many of them still have low self-efficacy. The aim of this study was to identify the relationship between knowledge and self-efficacy in providing first aid for traffic accidents among adolescents in Sanur Kauh Village. This research was a quantitative research with a descriptive correlative design using a cross-sectional approach. One hundred and twelve members of STT were selected as the sample through purposive sampling technique. Data were collected using questionnaires about knowledge and self-efficacy. Bivariate analysis was carried out using the Spearman Rank test. The whole respondents of this study were in the adolescence age range (16-24 years old) with majority of male respondents (54,5%) and senior high school as the latest educational background (62,5%). The results showed that most of the respondents (52%) has sufficient knowledge and high self-efficacy. Statistical test results showed that p value = <0,001; r = 0,754, which means there was a strong positive relationship. In conclusion, the higher the knowledge, the higher the self-efficacy in providing first aid for traffic accidents.